The Oxford handbook of organizational change and innovation - Poole, Marshall Scott, 1951-; Van de Ven, Andrew H. (Oxford : Oxford University Press, 2021)
Organizational change and innovation are central and enduring issues in management theory and practice. Dramatic changes in population demographics, technology, competitive survival, and social, economic, and environmental health and sustainability concerns means the need to understand how organizations repond to these shifts through change and innovation has never been greater. Why and what organizations change is generally well known; how organizations change is therefore the central focus of this handbook. It focuses on processes of change - or the sequence of events in which organizational characteristics and activities change and develop over time - and the factors that influence these processes, with the organization as the central unit of analysis.
Introduction: Central Issues in the Study of Organizational Change and Innovation / Andrew H. Van de Ven, Marshall Scott Poole -- Social Movements and Organizational Change / Gerald F. Davis, Eun Woo Kim -- Becoming an Agent of Change / Craig Prichard, W. E. Douglas Creed -- Stakeholder Model of Change / Laurie Lewis -- The Life Cycle Process Model / Marshall Scott Poole, Andrew H. Van de Ven -- Hedging: Organziational Responses to the Formulation, Implementation, and Enforcement of Government Mandated Changes / Alfred Marcus, Joel Malen -- Organizational Routines and Organizational Change / Brian T. Pentland, Kenneth T. Goh -- Evolutionary Dynamics of Organziational Populations and Communities / Joel A. C. Baum, Hayagreva Rao -- VSR Models of Change as Normative Practical Theory / Cara C. Maurer, Anne S. Miner, Mary Crossan -- Microfoundations of Innovation as Process: Usher's Cumulative Synthesis Model / Raghu Garud, Marja Turunen -- Historical Currents in Scholarship of Organization Change / W. Warner Burke -- Conceptualizing Organizational Change through the Lens of Complexity Science / Kevin J. Dooley -- Landscape Models of Complex Change / Daniel Albert, Martin Ganco -- Discontinuous Change in Organizations and Fields / Vibha Gaba, Alan D. Meyer -- Diffusion of Innovations / James W. Dearing -- Institutional Change / Evelyn Micelotta, Michael Lounsbury, Royston Greenwood -- Processes of Emergence and Change in Industry and Ecosystem Infrastructure / Jennifer L. Woolley -- Interorganizational Network Change / Michelle Shumate, Zachary Gibson -- Time and Temporality of Change Processes: Applying an Event-based View to Integrate Episodic and Continuous Change / Tor Hernes, Anthony Hussenot, Kätlin Pulk -- Must We Change?: The Dark Side of Change and Change Resistance / Theodore E. Zorn, Jennifer Scott -- Emotionality and Change / Quy Nguyen Huy, Timo O. Vuori -- Dualisms and D
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 4, 2021).
Keywords: Organizational change